Metode Penyelesaian Hadis Mukhtalif Tentang Larangan Menikah Pada Saat Ihram - Nuronia, Izza; Umar, Atho'ilah (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
This research originated from the emergence of concerns and ambiguity of the author who had minimal understanding of the methods and steps for completing mukhtalif hadith. The Mukhtalif hadith is a hadith that outwardly appears to be contradictory or contradictory (with other hadiths). To resolve the contradiction between one hadith and another, a method is needed to solve the hadith. The first procedure for this study is to determine the theme to be discussed, and after that conduct research on the method of completing the hadith contained in the theme, study the various meanings of the syarah hadith on the theme above, and complete the discussion with hadiths or verses of the Qur'an as supporting and reinforcing, and drawing conclusions with scientific arguments. In this writing using the library research method (library research), as well as other supporting documents that are in line with the main theme in this research, while the object of this research is al-Kutub al-Sittah, Kitab Fath al-Baari 'ala Sharh Sahih Al- Bukhari, and other supporting hadith books. The purpose of this paper is to gain an understanding of the formulation of the method used by muhaddisin and fuqaha' in solving mukhtalif hadiths, one of which is the hadith regarding the prohibition of marrying during ihram (hajj). The results of this study indicate an understanding of the completion of the hadith regarding the prohibition of marrying during ihram, in order to gain a more perfect understanding for readers and writers.